Development of the Korean Medicine Core Outcome Set for Facial Palsy: herbal medicine treatment of patients with facial palsy in primary clinics - Kim, Soo-Dam; Kim, Sungha; Son, Mi Ju; Cha, Jiyun; Kim, Pyung-Wha; Ko, Mi Mi; Jang, Soobin; Yang, Changsop; Lee, Myeong Soo (Frontiers in Medicine, 2024)
Introduction Facial palsy (FP) significantly affects the quality of life of patients and poses a treatment challenge in primary healthcare settings. This study aimed to develop a Korean medicine (KM) core outcome set (COS) for FP, with a focus on evaluating the effectiveness of herbal medicine (HM) treatments in KM primary clinics. Methods Outcomes and effect modifiers related to FP treatments were initially identified through related review articles. Subsequently, experts in the field took part in three rounds of modified Delphi consensus exercises to refine and prioritize these outcomes and effect modifiers. Additionally, primary KM clinicians were involved in a Delphi consensus round to assess the suitability and feasibility of the proposed COS in real-world clinical settings. Results The initial review of related literature identified 44 relevant studies, resulting in an initial selection of 23 outcomes and 10 effect modifiers. The expert consensus process refined these to 8 key outcomes and 6 effect modifiers, which established the foundation of the COS-FP-KM. Subsequently, primary KM clinicians confirmed the practicality and applicability of the COS, endorsing its suitability for use in KM primary clinics. Conclusion The COS-FP-KM establishes a standardized approach for assessing HM treatment effectiveness in FP patients in KM primary clinics. The COS-FP-KM encourages consistent outcome reporting and enhances patient care quality. Future work should aim to integrate broader stakeholder perspectives to refine and validate the COS further.